Orphan Drug Pricing: An Original Exponential Model Relating Price to the Number of Patients - Andrea Messori (MDPI AG, 2016)
In managing drug prices at the national level, orphan drugs represent a special case because the price of these agents is higher than that determined according to value-based principles. A common practice is to set the orphan drug price in an inverse relationship with the number of patients, so that the price increases as the number of patients decreases. Determination of prices in this context generally has a purely empirical nature, but a theoretical basis would be needed. The present paper describes an original exponential model that manages the relationship between price and number of patients for orphan drugs. Three real examples are analysed in detail (eculizumab, bosentan, and a data set of 17 orphan drugs published in 2010). These analyses have been aimed at identifying some objective criteria to rationally inform this relationship between prices and patients and at converting these criteria into explicit quantitative rules.